(untitled) (Construction Economics and Building, 2019)
The issue of whether contracts promote innovation and sustainability is an important but overlooked aspect for achieving energy and environmental targets, as well as for creating smart and sustainable cities. In this article, based on the principle/agent problem and Holmström and Milgrom’s work on optimal contracts it is argued that the current general conditions of architectural and engineering consulting agreements in Sweden (ABK 09)—a standard type of contract often used in developer/consultant relations—may not incentivize choices that support the long-term goals of society. Furthermore, although this exploratory study specifically analyses a Swedish standard contract, the question of how contractual incentive structures can optimize real-world performance is a general one, and thus the article’s findings have general applicability. This exploratory study also points to further research into how contractual structures impact climate-neutral buildings. In this way, Swedish consultants who use ABK 09 are incentivized to include low-risk, well-proven, and widely used technologies in order to minimize risks for themselves. This study contributes to resolving this dilemma by suggesting how ABK 09 could be restructured to change the balance between incentives and risk and incentivize innovation and sustainability. As mentioned above, the current study operates at a theoretical level. It discusses six possible changes that would better align the contract with the societal goals of innovation and sustainability.